ILRI research travelling further than ever before - Scott, R. Bruce (International Livestock Research Institute, 2011)
Bruce Scott, Director of Partnerships and Communications (P&C) at ILRI introduces the aims and objectives of the annual P&C retreat held in Addis Ababa in January 2011: Looking back on the past year, setting priorities for the coming year. The key issue was how we ensure that the outputs of ILRI research travel beyond the usual places ... to reach a much wider range of people and partners. This past year, we made the shift from an organization that relied on paper to one that more and more works in a virtual environment. The challenge now is to see how we can stretch ourselves even further!